Earthquakes and very deep groundwater perturbation mutually induced - Dugin Kaown; Kang-Kun Lee; Jaeyeon Kim; Jeong-Ung Woo; Sanghoon Lee; In-Woo Park; Daeha Lee; Jin-Yong Lee; Heejung Kim; Shemin Ge; In-Wook Yeo (Scientific Reports, 2021)
Abstract We report unique observations from drilling and hydraulic stimulation at a depth of approximately 4.3 km in two Enhanced Geothermal System (EGS) wells at the Pohang EGS site, South Korea. We surveyed drilling logs and hydraulic stimulation data, simulated pore pressure diffusion around the fault delineated by seismic and drilling log analyses, conducted acoustic image logging through the EGS wells, observed significant water level drops (740 m) in one of the two EGS wells, and obtained hydrochemical and isotopic variation data in conjunction with the microbial community characteristics of the two EGS wells. We discuss the hydraulic and hydrochemical responses of formation pore water to a few key seismic events near the hypocenter. We focused on how the geochemistry of water that flowed back from the geothermal wells changed in association with key seismic events. These were (1) a swarm of small earthquakes that occurred when a significant circulation mud loss occurred during well drilling, (2) the MW 3.2 earthquake during hydraulic stimulation, and (3) the MW 5.5 main shock two months after the end of hydraulic stimulation. This study highlights the value of real-time monitoring and water chemistry analysis, in addition to seismic monitoring during EGS operation.